Penentuan Kecamatan Basis Komoditas Padi Menggunakan Analisis LQ Dan DLQ di Kabupaten Kutai Kartanegara - Hikmah Dwi Nurfani; Ajeng Nugrahaning Dewanti; Devi Triwidya Sitaresmi (Jurnal Penelitian Pertanian Terapan, 2020)
One of the directions for the development of Kutai Kartanegara Regency is the development of food based on local raw materials to increase competitiveness, then the direction for its development is through food crop agribusiness agriculture (Regional Long-Term Development Plan (RPJPD) of Kutai Kartanegara Regency 2005-2025, 2010). The rice commodity has a contribution percentage above 50% and is more stable than other commodities in the last 3 (three) years, 2016-2018 (Department of Agriculture and Animal Husbandry, Kutai Kartanegara Regency, 2020). However, there has been a decline in the production of rice commodities by 3% annually in five years, starting from 2013-2017 in Kutai Kartanegara Regency (Department of Agriculture and Animal Husbandry, Kutai Kartanegara Regency, 2020). So that the research aims to analyze the rice-producing sub-districts so that the government or the authorities can develop agricultural potential, especially rice commodities in Kutai Kartanegara Regency to the fullest. The method of analysis is to use LQ and DLQ analysis in each District in Kutai Kartanegara Regency. The result of the analysis is that rice commodity becomes a basic commodity in Loa Kulu, Sebulu, Tenggarong Seberang, Anggana, and Muara Kaman Districts.